Single-emission dual-enzyme magnetosensor for multiplex immunofluorometric assay of adulterated colorants in chili seasoning. (1st January 2022) - Guan, Tian; Jiang, Zhuo; Liang, Zaoqing; Liu, Yingju; Huang, Weijuan; Li, Xiangmei; Shen, Xing; Li, Mengting; Xu, Zhenlin; Lei, Hongtao
Graphical abstract: Highlights: Simple optical structure but high multiplexing capacity was achieved in this work. A discriminant analysis was developed to precisely distinguish Sudan Ⅰ and Sudan Ⅱ. Easy operation and convenient signal readout was implement in this work. Abstract: In this work, a single-emission, dual-enzyme immunofluorometric magnetosensor was fabricated to simultaneously detect three illegal colorants in chili seasoning. Specifically, two enzymatic reactions catalyzed by horse radish peroxidase-labeled Rhodamine (RhB) antibody and glucose oxidase-labeled Sudan dyes (SuDs) antibody were performed within a functional microfluidic chip, leading to production of strongly fluorescent Resorufin. In addition, a compact analyzer assisted by a smartphone was developed to quantify signals. Compared with the available multiplex optical biosensors, this work demonstrated four superiorities: 1) Simple optical structure. Only single wavelength excitation/emission module was needed; 2) High multiplexing capacity through spatial resolution and signal resolution; 3) Precise determination by discriminant analysis; 4) Easy-operated and high-throughput parallel detection on 16-channel chips. Ultralow detection limits for RhB (0.0072 ng/mL), Sudan I (0.0040 ng/mL) and Sudan II (0.0260 ng/mL) were obtained by this magnetosensor, which opens a new approach in field detection of multiplex illegal dyes in food system.